O INSTRUMENTO RECONTO ORAL E SUA INFLUÊNCIA NA AVALIAÇÃO DA COMPREENSÃO LEITORA - SILVA, GISELI CORDEIRO DA (2023)
Comprehension is undoubtedly the inherent objective in any reading activity; it involves processes that relate linguistic, psycho cognitive, and psychosocial knowledge with influential factors in reading comprehension (SIQUEIRA; ZIMMER, 2006; KLEIMAN, 2008; GIRALDELLO, 2016). In this research, linguistic competence, prior knowledge, knowledge of different textual types, reading strategies, motivation, working memory, and inferences were selected as influential factors for understanding. Considering the processes and factors that influence reading comprehension and its evaluation possibilities, the objective of this study was to investigate how Oral Retelling is used to assess reading comprehension at national and international contexts of research, having as theoretical support the areas of psycholinguistics, linguistics, and cognitive psychology. To achieve this objective, studies conducted within the 2012-2022 period published in national and international journals stratified as A1, A2, B1, and B2 in the Brazilian ranking system Qualis Capes, in the Language/Linguistics, Education and Psychology areas were used as data sources. A bibliographic review was carried out based on the Content Analysis method by Bardin (2016). Eight studies were selected for qualitative analysis. The analysis considered the ways Oral Retelling was used (alone or combined with other instruments), the textual types (narrative, expository), the relationship of the comprehension factors considered for analysis, the age range and education level of the participants, and the observation of factors and processes related to reading comprehension. In the selected articles, Oral Retelling was often used with other assessment instruments, such as questionnaires and comprehension tests. The retellings were recorded and transcribed for later analysis and categorized by rubrics and classification scores. The most prominent comprehension factors that were revealed in the studies were the linguistic competence, the prior knowledge, and the use of working memory. Oral retelling was mostly used with 6- to 10-year-old participants, which comprises the Elementary School level. It was possible to note that oral retelling proved to be a versatile and reliable instrument in the assessment of reading comprehension.